دور تمويل صندوق رعاية النشء والشباب والرياضة في الارتقاء بواقع الرياضة اليمنية - النظاري, محمد حسين (Université de M'sila, 2011)
يعد صندوق رعاية النشء والشباب والرياضية في اليمن، إحدى الوسائل المهمة التي ساعدت هذه الفئات على تنمية وصقل مواهبهم وإبداعاتهم، فقبل إنشاءه سنة 1996م كانت الرياضة اليمنية تفتقر إلى الموارد التي تمكنها من الارتقاء بمستوياتها في مختلف الألعاب، حيث شهد هذه القطاع قبل هذه الفترة ندرة في المنشآت الرياضية، وقلة في تحضيرات الأندية والمنتخبات، وعدم احتضان البطولات الخارجية، وقد تغير الحال كثيرا حيث شهد قطاع الرياضة نموا مطردا سواء من حيث البنية التحتية أو إعداد الشباب. وهدف البحث للتعرف على المكانة التي يحتلها النشء والشباب في المجتمع.، ورصد مجمل الإنجازات التي حققها الصندوق، والوقوف على التحديات والصعوبات التي يعاني منها، ووضع التوصيات المناسبة لمعالجتها. وتوصل الباحث إلى وجود بيئة تشريعية جيدة تتعلق باهتمام الحكومة اليمنية وأهمها صندوق رعاية النشء والشباب والرياضة، الذي ساهم في إنشاء العديد من الأندية والاتحادات الرياضية، كما تبين أن سوء تسيير الإدارات المتعاقبة عليه أحدث عجزاً كبيراً في ميزانيته، من خلال عدم متابعتها المستمرة للجهات المسئولة عن سداد ما عليها من رسوم بحسب ما اقره القانون عليها . Abstract: The Fund for the Care of children and youth and sports in Yemen, one of the important means which have helped these groups to develop and refine their talents and their creations, before its establishment in 1996 the sport of Yemen lacks the resources to improve the levels in the various games, where he witnessed this sector before this period, a dearth of sports facilities, and lack of preparations in the clubs and teams, and not embrace the State Championships, has changed as much as the sports sector has witnessed steady growth both in terms of infrastructure or the preparation of young people. The objective of this research to identify the position occupied by the children and youth in the community., And monitor the overall achievements of the Fund, and identify the challenges and difficulties faced by them, and make appropriate recommendations to address them. And the researcher to the existence of a legislative environment good about interest the government of Yemen, the most important fund-care children and youth and sports, which contributed to the creation of numerous clubs and sports associations, and show that the ill conduct of successive administrations was the latest large deficit in its budget, by not constant follow up to those responsible for pay their fees according to the law passed by them
Keywords: التمويل- صندوق رعاية النشء والشباب والرياضة